Fisheries guidelines in the conduct of yield of trials of fisheries technology and for the assessment - Fortes, R.D., Fortes, N,R. and Pagbilao, C.R (Department of Agriculture, Bureau of Agricultural Research, 1991)
Farm Research Manual Module 8